In vitro Regeneration of Gerbera (Gerbera jamesonii) in SAU Tissue Culture Medium - Shoma, Zannatun Naium; Hoque, Md. Ekramul; Masror, Talha Zubair; Hossain, Md. Jamal; Huq, Homayra (European Journal of Applied Sciences, 2026)
In vitro regeneration potentiality of Gerbera (Gerbera jamesonii) flower was evaluated in ammonium nitrate free SAU Plant tissue culture medium. The most population MS (1962) medium and MS powder (Duchefa Biocheme, The Netherland) were used as two check treatments. Data were collected on callus induction, days to shoot initiation, multiple shoot regeneration, shoot length, number of leaves, root number and root length. Among the treatments, MS powder (T1) showed the best shoot performance for producing the highest number of shoots (23.00), longest shoots (7.40 cm) and maximum leaves (5.33) at 42 days after inoculation. The second highest performance showed by the SAU Tissue Culture medium which was very close to MS powder and non significant for most of the traits under study. The SAU TC showed the highest root number (7.33) and length (6.97 cm). Regenerated plantlets showed 95% survival under controlled conditions and 75% in field acclimatization. The findings validate the SAU TC medium as a safe, economical and effective alternative to MS media for large-scale in vitro propagation of Gerbera in Bangladesh.